2015
DOI: 10.1680/si.14.00002
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants coated with a durable and antibacterial film

Abstract: Dental implants coated with a durable and antibacterial film Vogel et al. embedded between two layers of PP by means of subsequent plasma polymerization and metal evaporation steps. The double PP/Ag/PP layer can be directly deposited on titanium implants, whose in vivo biocompatibility within soft tissues has been investigated in Ref. 13 .Building up on these previous results, in this article, we investigate the performances of a similar PP/Ag/PP-layered coating material (briefly, PP+Ag) toward the adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…Hyaluronic acid combined with chitosan forms polyelectrolyte multilayers (PEMs) with strong antimicrobial activity against S. aureus 99) . Plasmapolymerized hexamethyldisiloxane reduces bacterial adhesion of E. coli 92) . In contrast, silicon-containing polymeric surfaces do not exhibit any bactericidal activity compared to control surfaces 97) .…”
Section: Polymeric Coatingsmentioning
confidence: 99%
“…Hyaluronic acid combined with chitosan forms polyelectrolyte multilayers (PEMs) with strong antimicrobial activity against S. aureus 99) . Plasmapolymerized hexamethyldisiloxane reduces bacterial adhesion of E. coli 92) . In contrast, silicon-containing polymeric surfaces do not exhibit any bactericidal activity compared to control surfaces 97) .…”
Section: Polymeric Coatingsmentioning
confidence: 99%
“…(2016) Creation and Evaluation of Construction Guidelines Using CFD for Low Pressure Plasma Gas Feed-in Systems to Homogenize the range of industrial fields such as aircraft, automotive and medical devices for the application of functional coatings e.g. anti-bacterial, anti-scratch, anti-reflection and enhance wear resistance [1] [2] [3] [4]. Within the PECVD process the substrate allocated in a vacuum chamber is exposed to the influence of the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial adhesion to the surface of implants may result in peri-implant diseases and cannot always be avoided by sterilization before implantation. AgNPs coating produced a strong antibacterial effect on the titanium surface by inhibiting the adhesion of bacteria (Massa et al, 2014;Matsubara et al, 2015;Mishra et al, 2015;Qin et al, 2015;Vogel et al, 2015). In our study, AgNPs were incorporated to the surface of dental alloys to improve their antibacterial properties, in order to further reduce the incidence of denture stomatitis and peri-implantitis.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, AgNPs have been used to enhance the antibacterial performance of dental materials (Qin et al, 2015;Vogel et al, 2015). AgNPs were added to composite resins and results demonstrated that, in sufficient concentrations, the presence of nanosilver significantly increased the resins' antibacterial performance (Fan et al, 2011;Ai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%